Pengaruh Kepuasan Transaksi Online Shopping Dan Kepercayaan Konsumen Terhadap Sikap Serta Perilaku Konsumen Pada E-Commerce - Iwan Sidharta; Boy Suzanto (STMIK Mardira Indonesia, Bandung, 2015)
The Influence Of Online Shopping Overall Satisfaction And Customer Trust On Attitudes And Behavior Of Online Shopping In E-Commerce. The purpose of this study was to determine the influence of customer satisfaction before and after the transaction as well as consumer confidence in consumer attitudes and behavior of e-commerce. Exploratory research methods used by respondents as many as 60 students who have done pemberlian online transactions on e-commerce has been determined. Data were analyzed using Structural Equation Modeling (SEM), component -based Partial Least Squares (PLS). The results showed that customer satisfaction when transacting effect on consumer confidence in shaping attitudes and behaviors to perform intention to use in e-commerce. Keywords: overall satisfaction; trust; attitude; usage behavior